PERSEPSI IBU RUMAH TANGGA (IRT) TERHADAP REVITALISASI POSYANDU DI JALAN LIMBUNGAN, RUMBAI, PEKANBARU - Muslima, Fikri; Ayub, Daeng; Wilson, Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Housewives' Perceptions (IRT) of Posyandu Revitalization Activities on Jalan Limbungan, Rumbai, Pekanbaru classified as positive. Benefits Providing thoughtful contributions to the housewives' perception (IRT) of Posyandu Revitalization Activities on Jalan Limbungan, Rumbai, Pekanbaru. This research is descriptive with a quantitative approach. The population in this study were 88 people. Sampling in this study using simple random sampling. The instrument used was a questionnaire containing 27 item statements. Perception, Housewife (IRT) Revitalization of Posyandu on Jalan Limbungan Rumbai, Pekanbaru was measured by indicators (1) accepting, (2) understanding and (3) assessing. The results of the study revealed that Perception, Housewife (IRT) Revitalization of Posyandu on Jalan Limbungan Rumbai, Pekanbaru was classified as positive. The highest mean at receiving 53.24, the mean indicator understands 43.57 mean indicators assessing 33.78 as high. Therefore, it can be stated that most housewives (IRTs) have a positive perception of the posyandu revitalization activities in terms of accepting, understanding, and evaluating.Key Words: Perception, Housewives, Revitalization, Posyandu.